Regulation and Mechanisms of L-Lactic Acid and D-Lactic Acid Production in Baijiu Brewing: Insights for Flavor Optimization and Industrial Application - Yabin Zhou; Jin Hua (Fermentation)
L-lactic acid and D-lactic acid are chiral forms of lactic acid that significantly influence the flavor and health-related properties of Baijiu. Their production during brewing is primarily driven by lactic acid bacteria (LAB), with L-lactic acid being favored at higher fermentation temperatures and by specific high-producing strains, while D-lactic acid predominates at lower temperatures and with limited microbial utilization. Various factors, including fermentation mash composition, microbial communities, and brewing conditions, affect the balance between these isomers. This review synthesizes recent research on regulating L- and D-lactic acid production in Baijiu brewing, highlighting advancements in raw material selection, fermentation starter composition, temperature control, LAB strain selection, and distillation techniques. It critically evaluates strategies aimed at increasing L-lactic acid content while minimizing D-lactic acid levels to optimize flavor and promote health benefits. This review aims to provide theoretical insights and practical guidance for controlling these chiral isomers in Baijiu production. By consolidating the latest findings, it serves as a resource for industrial applications, offering strategies to enhance lactic acid ratios, improve Baijiu flavor, and support sustainable development in the industry.